Regrown ohmic contact to GaN-based high electron mobility transistors - Tan, Eleen (Nanyang Technological University, 2023)
GaN-based High Electron Mobility Transistors have been of great interest for applications in high temperature, high frequency, high speed, and high power devices. GaN-based HEMTs have properties like wide bandgap, high saturation, and high critical breakdown field, making them favourable for further development and investigation. To realize high-performance AlGaN/GaN HEMT devices, good ohmic contacts with low resistivity are critical.